THE RELATIONSHIP BETWEEN EXERCISE FREQUENCY WITH THE MENSTRUAL CYCLE OF THE ADOLESCENT ON PENCAK SILAT GROUP - Machmudah -; Fitri Yanna; Pawestri - (Universitas Muhammadiyah Semarang, 2017)
Background : Excessive physical activity is one factor that can cause menstrual disorders. Disorders that can occur include the absence of menstruation (amenorrhea), bone thinning (osteoporosis), irregular menstruation orintermenstrual bleeding, abnormal growth of the uterine lining, and infertility (Asmarani, 2010). Wiarto (2013)explains that in sports discussed about menstruation is an irregular menstrual cycle (oligomenorrhea or reducedmenstrual frequency) or menstruation stops beyond 90 days (amenorrhea or absence of menstrual cycle). Thepurpose of the study: the purpose of the study is to determine the relationship between the frequency of exercise with menstrual cycle in adolescent girls SMAN in Purwokerto who follow the practice of pencak silat. Researchmethod: This research is a descriptive research with quantitative approach with total sample of 126 respondents,sampling technique is by non probability sampling technique that is by purposive sampling technique. Result ofresearch: The result of statistical test by using simple logistic regression shows that there is relationship betweenexercise frequency with menstrual cycle with p = 0,000 (p <0,05). Conclusion: This result suggests that excessive exercise is seen in terms of exercise frequency and duration of exercise leading to dysfunction in the hiothalamus leading to impairment of GnRH pulsatility that may inhibit FSH secretion. Suggestions: The suggestions that can be given here is necessary for further research with a larger sample size and consider the psychological condition and nutritional status of respondents Keywords: Dismenorhea, frequency of exercise